Towards a M&E toolkit for Egypt's agricultural development projects - Breisinger, Clemens; ElDidi, Hagar (2016)
Presentation by Clemens Breisinger (IFPRI) and Hagar ElDidi (AUC) on April 21, 2016 in Cairo, Egypt